Defence industry applications of autonomous agents and multi-agent systems - Pechoucek, Michal; Thompson, Simon G.; Voos, Holger (Whitestein series in software agent technologies and automatic computing, 2008)
This collection of recently published and refereed papers comes from workshops and colloquia held over the last two years. The papers describe the development of command and control systems, military communications systems, information systems, surveillance systems, autonomous vehicles, simulators, and HCI. The collection provides for the first time an overview of the most significant advances in the technology of intelligent agents.